Nursing Corpus and the Academic Collocation List - Mandić, Kaja (Corpora in Language Learning, Translation and Research: Proceedings of the International Conference Corpora in Language Learning, Translation and Research held at the University of Zadar (August 23–24, 2023), 2025)
Knowledge of frequent collocations is very important in the scientific discourse and writers should be familiar with collocations valued in a particular scientific discipline. Collocations enable English language learners to put words commonly used by native speakers to appropriate use in appropriate contexts. The study is based on the comparison of collocations from a corpus of articles written by native speakers of English and collocations from a corpus of English articles written by native speakers of Croatian, Bosnian, and Slovenian with the Academic Collocation List (ACL). The objective of the study is to extract the most frequent two-word collocations from the two nursing corpora and compare them with the ACL. The study will produce two corpora that are classified as specialized corpora. Both native and non-native corpora will include only English scientific articles from the field of nursing science. The results will be useful to generate a field-specific academic vocabulary list and teaching materials in order to strengthen learners’ academic reading and writing proficiency.